2021
DOI: 10.3390/ani11102969
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Flexibility in Canine Mammary Tumors: Implications of the Carnitine System

Abstract: Deregulation of fatty acid catabolism provides an alternative energy source to glycolysis for cancer cell survival and proliferation. The regulator enzymes of the carnitine system (CS), responsible for the transport of fatty acids across mitochondrial membranes for β-oxidation are deregulated in tumorigenesis. Recently, we found that Carnitine Palmitoyl Transferase 1 (CPT1), a crucial regulator of CS components, is expressed and dysregulated in canine mammary tumor (CMT) tissues and cells. In this study, we ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…The acetylation modification levels of these proteins were significantly up-regulated, while the crotonylation modification levels of these proteins were significantly up-regulated or down- regulated. Among the proteins with significant modification changes, liver carnitine palmitoyltransferase 1a (CPT1A) and peroxisome ABC transporter ABCD3 are essential in β-oxidation and peroxisome oxidation, respectively ( Cacciola et al., 2021 ; Violante et al., 2019 ). Existing studies have shown that ABCD3, acyl CoA oxidase 2 (ACOX2), Acaa1a, and Ehhadh proteins are the key regulatory enzymes of peroxisome oxidation ( Kersten and Stienstra, 2017 ; Nenicu et al., 2007 ), and the expression levels of CPT2, ACADVL, ACAA2, HADHA, ACADSB, and ACOX1 contribute to FAs β-Oxidation.…”
Section: Discussionmentioning
confidence: 99%
“…The acetylation modification levels of these proteins were significantly up-regulated, while the crotonylation modification levels of these proteins were significantly up-regulated or down- regulated. Among the proteins with significant modification changes, liver carnitine palmitoyltransferase 1a (CPT1A) and peroxisome ABC transporter ABCD3 are essential in β-oxidation and peroxisome oxidation, respectively ( Cacciola et al., 2021 ; Violante et al., 2019 ). Existing studies have shown that ABCD3, acyl CoA oxidase 2 (ACOX2), Acaa1a, and Ehhadh proteins are the key regulatory enzymes of peroxisome oxidation ( Kersten and Stienstra, 2017 ; Nenicu et al., 2007 ), and the expression levels of CPT2, ACADVL, ACAA2, HADHA, ACADSB, and ACOX1 contribute to FAs β-Oxidation.…”
Section: Discussionmentioning
confidence: 99%
“…Endogenous peroxidase was blocked with 0.3% hydrogen peroxide in absolute methanol for 30 min. Immunohistochemistry was performed by the streptavidin–biotin–peroxidase complex method using a commercially available kit as described elsewhere [ 13 ] (streptavidin–biotin–peroxidase method LSAB kit; Dako, Glostrup, Denmark). For this study, the available primary antibody against SIRT1 (mouse anti-human monoclonal antibody, 1:100, Biorbyt, Cambridge, UK, orb306144) was used.…”
Section: Methodsmentioning
confidence: 99%
“…Immunoreactivity was assessed by two pathologists (BR and MS) and graded according to the number of positive cells in 10 High Power Fields (40× objective and 10× ocular; grade 0: no positive cells; 1: 10%; 2: 10.1-30%; 3: 30.1-60%; 4: > 60.1%), and the intensity of staining was classified as weak (1), moderate (2), or strong (3). Then, a combined immunoreactivity score (IR score) was calculated for each sample by multiplying the values of these two categories, ranging from 0 to 12 according to previous studies [13,21,22].…”
Section: Immunohistochemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…The carnitine shuttle system is a key player in lipid catabolism since it allows for the translocation of fatty acids from the cytoplasm into the mitochondria for further oxidation and ATP production. Carnitine acylcarnitine translocase (CACT), carnitine palmitoyl transferase 2 (CPT2), and carnitine O-acetyltransferase (CrAT) have been found to be overexpressed in CMTs in cell lines and tissue compared with normal conditions, except for decreases observed in poorly undifferentiated, higher-grade CMTs [80]. In the same manner, carnitine palmitoyl transferase 1 A (CPT1A), a rate-limiting enzyme of fatty acid oxidation located in the outer mitochondrial membrane, has been reported as overexpressed in differentiated CMTs compared with normal tissue both in vivo and in vitro, whereas a decrease in CPT1A expression has been observed in less differentiated tumors [81].…”
Section: Lipid Metabolismmentioning
confidence: 99%